Interleukin-6 for the diagnosis of ovarian torsion: A systematic review and meta-analysis. (July 2013) - Christopoulos, G.; Goubet, S.; Kelly, T.
<x xml:space="preserve">Abstract</x> Ovarian torsion may have significant fertility implications. Interleukin-6 is a pro-inflammatory cytokine, which may act as a helpful diagnostic test. Our objective was to investigate the accuracy of serum interleukin-6 in the diagnosis of ovarian torsion in women with ultrasonographic evidence of an ovarian cyst. An electronic search of published data, unpublished dissertations, theses and conference proceedings was performed. The systematic review involved observational studies. The studies had to provide data to construct 2 × 2 tables. A modified QUADAS tool was used to assess the quality of studies. Sensitivity, specificity, positive and negative predictive value, likelihood ratios and diagnostic odds ratios were calculated. Three studies were identified. Two were included in the meta-analysis. The prevalence of torsion was 30% (21/70). The pooled sensitivity was 85.1% and the pooled specificity was 84.1%. Although further cohort studies would be required, there may be a role for interleukin-6 in the diagnosis of ovarian torsion.